Optimization of sorting efficiency of size grading machine using oscillating sieve with swing along width direction - Thatchapol Chungcharoen; Warunee Limmun; Watcharapong Chanpaka; Naruebodee Srisang (My University, 2019)
Grading according to the sizes is an important value adding technique for Robusta green coffee bean. Mechanical grading can increase the sorting efficiency and the need for workers is decreased. Therefore, the sorting efficiency of size grading machine was optimized based on inclined angle and oscillating speed. The Response Surface Methodology (RSM) combined with central composite design (CCD) was applied in the optimization of the sorting efficiency of the machine. A quadratic model was suggested for the sorting efficiency of size grading machine. The results showed that the optimum operating parameters for size grading machine using oscillating sieve with swing along width direction were inclined angle of 5.06 degree and oscillating speed of 183.28 rpm with a sorting efficiency of 79.99%. The high correlation coefficient (R 2 = 0.9676) indicated that the data predicted using RSM were in good agreement with the experimental results.
Keywords: Sieve (category theory); Grading (engineering); Sieve analysis; Agricultural Engineering and Mechanization